PENERAPAN KOMPETENSI PEDAGOGI GURU ABAD 21 DALAM PEMBELAJARAN DARING - Hannah Dea; Wiputra Cendana; Bill Areal Sharon Djaduhu Daeli (Program Studi PGSD Universitas Flores, 2021)
In online learning, there are several problems for both teachers and students. namely, skills in utilizing technology, limited facilities and infrastructure, interactive media. The solution is the role of the teacher in designing learning with pedagogical competence in the 21st century. The teacher must use effective and interactive technology in communicating with students. The purpose of this study is to describe the efforts of teachers in applying the pedagogical competences of 21st century teachers in online learning through 3 learning components, namely materials, media and learning methods. The research method used descriptive qualitative with supporting data in the form of lesson plans, reflection sheets, and teacher feedback. Data collection techniques used observation sheets, lesson plans, teaching reflection, teaching feedback and documentation. The author uses feedback from teaching journals and reflection journals after the teaching process as the main data. Supporting sources are scientific journals and books that correspond to the problems the author finds. Analyzing data, researchers looked for solutions to problems that occur in teaching practice. The solution was for the teacher to design attractive learning methods, present learning materials by involving students, and utilizing technological media in the learning process. As a result, obstacles in online learning can be overcome through teacher pedagogical competences in the 21st century. The suggestion are that teachers should continue to improve themselves in developing their own pedagogical competences, and have effective communication with students.